STUDY OF MSSBAUER SPECTROSCOPY ON FE90-XMN10ALX (X = 10, 20, 30, AND 40 AT. %) BCC PHASE NANOCRYSTALLINE ALLOYS - Tarigan, Kontan; Ginting, Masno (LIPI Press, 2013)
Nanocrystalline alloys of Fe90-xMn10Alx (x= 10, 20, 30, and 40 at. %) were prepared via mechanical alloying technique using Fe, Mn, and Al commercial powders with a 48-hr milling time. Mssbauer spectroscopy show hyperfine field distribution (HFD) varied according to Fe content. HFD with concentration of x = 10, 20 dan 30 at. % repealed sexted structure and to be narrow with increasing of concentration x, and HFD shifted to smaller field value, i. e. 298.6, 262.6 and 240.8 kOe. For smallest Fe content (x = 40 at. %) repealed singlet spectrum with positive isomer (? ? 0,067 mm / s) without detected the HFD.